The assessment of cholinesterase from the liver of Puntius Javanicus as detection of metal ions - Sabullah, Mohd Khalizan; Sulaiman, Mohd Rosni; Abd Shukor, Mohd Yunus; Syed, Mohd Arif; Shamaan, Nor Aripin; Khalid, Ariff; Ahmad, Siti Aqlima (Hindawi Publishing Corporation, 2014)
Crude extract of ChE from the liver of Puntius javanicus was purified using procainamide-sepharyl 6B. S-Butyrylthiocholine iodide (BTC) was selected as the specific synthetic substrate for this assay with the highest maximal velocity and lowest biomolecular constant at 53.49 µmole/min/mg and 0.23 mM, respectively, with catalytic efficiency ratio of 0.23. The optimum parameter was obtained at pH 7.5 and optimal temperature in the range of 25 to 30°C. The effect of different storage condition was assessed where ChE activity was significantly decreased after 9 days of storage at room temperature. However, ChE activity showed no significant difference when stored at 4.0, 0, and −25°C for 15 days. Screening of heavy metals shows that chromium, copper, and mercury strongly inhibited P. javanicus ChE by lowering the activity below 50%, while several pairwise combination of metal ions exhibited synergistic inhibiting effects on the enzyme which is greater than single exposure especially chromium, copper, and mercury. The results showed that P. javanicus ChE has the potential to be used as a biosensor for the detection of metal ions.